Digital Twin: Exploring the Intersection of Virtual and Physical Worlds - Devika Menon; Bharath Anand; Chiranji Lal Chowdhary (IEEE Access, 2023)
The potential of digital twin technology to generate virtual models and simulations of real assets and processes has contributed to the widespread adoption of this technology across a variety of business sectors. As a result, performance, cost savings, and overall efficiency have all seen significant improvements. By conducting a study of the academic literature and previous research, this article offers readers an introduction to the origins, evolution, and applications of digital twin technology. This paper looks at the different kinds of digital twins, the advantages, and disadvantages of using them, and the causes that have contributed to their rising popularity. Case examples illustrating effective implementations of digital twin technology in industry and healthcare are included in the article. An overview of digital twin technology and its prospective applications in several industries is provided in this paper. This paper intends to contribute to the current understanding of digital twin technology and its potential impact by discussing the advantages, limitations, and prospects for further study and development.